STRATEGI DINAS PERDAGANGAN DAN KOPERASI USAHA KECIL DAN USAHA MENENGAH (UU NO. 20 TAHUN 2008) DI DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH MELALUI RETRIBUSI PELAYANAN PASAR DI DOLOKSANGGUL KABUPATEN HUMBANG HASUNDUTAN - Simamora, Anna Maria; Rajagukguk, Jonson; Tobing, Artha Lumban (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to examine the development strategy of Micro, Small, and Medium Enterprises (MSMEs) in Humbang Hasundutan Regency and the role of the Industry and Trade Service in improving this sector in accordance with the provisions of Law No. 20 of 2008. MSMEs are considered the backbone of the regional economy because they are able to open up new business opportunities and survive during the economic crisis with direct connections to the community. This study identifies the advantages of MSMEs such as technological innovation, market flexibility, and roles in absorbing labor. However, various obstacles such as complicated licensing processes and limited market access are still major obstacles. Through qualitative research methods, data were collected through direct observation and interviews with MSME actors and related parties. In-depth analysis revealed that market service fees have the potential to be a significant instrument in increasing Local Revenue (PAD) and MSME development. This study concludes the importance of strategic support from the Industry and Trade Service to overcome existing obstacles, and recommends more effective development strategies to advance the local economy in Humbang Hasundutan Regency.